2017
DOI: 10.4172/2375-4494.1000333
|View full text |Cite
|
Sign up to set email alerts
|

Social Functioning and Mental Wellbeing in 13- to 15-year-old Adolescents in Iran and Finland: A Cross-cultural Comparison

Abstract: Objectives: To investigate social functioning and mental wellbeing in 13-15 year-old adolescents in Iran and Finland, in order to explore potential cultural and gender-based differences during early adolescence. Methods:One thousand and one (1001) adolescents from Iran and 2205 adolescents from Finland (age range 13-15 years) filled in a questionnaire consisting of the following scales: the Mini Direct and Indirect Aggression Scale (Mini-DIA), the Self-Efficacy Questionnaire for Children (SEQ-C), the School Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…The Emotional Self-efficacy (ESE) subscale of the Self-Efficacy Questionnaire for Children (SEQ-C), developed in the Netherlands by Muris [12], assesses perceived ability to cope with negative emotions. It has shown reliability (α = alpha) values from 0.54 [13] to 0.90 [14]. Its scores diverge from depression, anxiety, and panic/somatic problems [12,15], but converge with prosocial behavior [13], quality of family climate [16], life satisfaction [17], cognitive flexibility [18] hope, effort, and positive mood [19].…”
Section: Introductionmentioning
confidence: 99%
“…The Emotional Self-efficacy (ESE) subscale of the Self-Efficacy Questionnaire for Children (SEQ-C), developed in the Netherlands by Muris [12], assesses perceived ability to cope with negative emotions. It has shown reliability (α = alpha) values from 0.54 [13] to 0.90 [14]. Its scores diverge from depression, anxiety, and panic/somatic problems [12,15], but converge with prosocial behavior [13], quality of family climate [16], life satisfaction [17], cognitive flexibility [18] hope, effort, and positive mood [19].…”
Section: Introductionmentioning
confidence: 99%
“…Khademi et al, [9] explored the social function and mental wellbeing in a sample of Iranian and Finnish adolescents in a trial to delineate the impact of culture and gender on such issues. They found that studied Iranian and Finnish boys despite their higher societal status, experienced more stress in their schools than their female counterparts.…”
Section: Editor-notementioning
confidence: 99%